Projetos pedagógicos do curso técnico de nível médio em informática na forma integrada do IFAM: do escrito ao vivido pelos diferentes sujeitos - Silva, Rosangela Santos da (2017)
The main purpose of this research was understanding the development context of the Integrated High School (hereinafter IHS) at the Federal Institute of Education, Science and Technology of Amazonas, in the perspective of the Middle Level Technical Course in Information Technology in the Integrated Form of the Manaus Centro, Coari and São Gabriel da Cachoeira campi, considering the period from 2012 to 2017. We intended to investigate the conception of IHS that permeates the Pedagogical Projects of the Middle Level Technical Courses in Information Technology in the Integrated Form of the aforementioned campi. We also intended to investigate the IHS conception that permeates the pedagogical practice of the different subjects who work in these courses and to identify what actions the educational management of IFAM, both systemic and local, has promoted to develop and enhance the pedagogical practice of the IHS teachers in line with the policies, conceptions and principles which guide its development in the perspective of Integral Human Formation. The theoretical pillars of this research process were anchored in the studies of Araujo (2008), Ciavatta (2010), Frigotto (2005; 2013), Garcia (2009), Machado (2008; 2010; 2011), Moura (2008; 2010; 2013; 2014), Ramos (2007; 2010; 2011), Santomé (1998), Saviani (2003) and Silva (2013), among others who discuss the work-education relationship. The social actors of the research consisted of teachers who work in the general formation and professional formation of the aforesaid courses; of professionals who work directly in the local pedagogical management of the above-mentioned campi and of top managers of the Pro-Rectory of Education whose work is related to the Middle Level Technical Professional Education (hereinafter MLTPE). As for the methodological course undertaken in this qualitative research, we gathered the data by conducting documentary research and by applying online questionnaire. The process of analysis and interpretation of the data was anchored in the analytical tool of Discourse Textual Analysis by Moraes and Galiazzi (2016), and resulted in the following categories: IHS in the Pedagogical Projects of Course; IHS in the experience of the different subjects; and IHS in the writings and actions of the top management. The research findings suggest that among the social actor of the research and the analyzed documents, there are different understandings of IHS conception, which signalizes a partial understanding of the philosophical, pedagogical, political and methodological proposal of the IHS. They also suggest that the materialization of the IHS is still partial within the campi, and that both local management and the systemic macro must develop effective actions in search of this materialization due to the fact that the actions are configured as timid and little systematized. In order to change this scenario, it is necessary to develop continuous and propositional formative processes for the teachers who work with IHS. Based on this need, the product of this investigation is a formative proposal for teachers who work with MLTPE and IHS. The proposal was implemented by means of the moodle platform, configured in a 120 hours Continuous Training Course for teachers, focused on the IHS theme. This research may influence positively the attitude towards the materialization of the IHS proposal, giving students the opportunity to build Integral Human Formation and their political, economic and cultural citizenship.